Yard crane dispatching based on real time data driven simulation for container terminals - Guo, Xi (2011)
This paper studies the problem of real time yard crane dispatching in container terminals. Many technologies, including transponders, RFID and GPS have been used in the container terminal setting for real-time tracking of terminal equipment. A judicious integration of real-time data into the yard crane management system will allow better utilization of terminal resources to improve overall terminal productivity. We propose a yard crane dispatching algorithm based on real time data driven simulation to solve the problem of yard crane job sequencing to minimize average vehicle waiting time. The algorithm will produce optimal operation sequence for each planning window. Several policies to select jobs to form the planning window are also proposed. Our simulation results show that dispatching yard crane based on real time data driven simulation is of great value in improving yard crane performance in 3 scenarios with different vehicle arriving patterns and our results are 10% worse off a loosely estimated overall optimal performance result.